AI-Integrated Project-Based Learning in Primary Education: A Systematic Review of Digital Literacy and Creativity - Een Nur Robithoh; Mustaji Mustaji; Alim Sumarno (CV. Media Inti Teknologi, 2026)
Background: The integration of Artificial Intelligence (AI) in education has grown rapidly, yet its implementation within the Project-Based Learning (PjBL) model at the primary school level still faces challenges.Aims: This Systematic Literature Review (SLR) aimed to synthesize the empirical trends, effectiveness, and pedagogical roles of AI integration within the PjBL syntax, focusing specifically on its dual impact on primary school students' digital literacy and creativity.Methods: Guided by the PRISMA 2020 protocol, this study analyzed 16 high-quality empirical articles (2021–2025) identified through ScienceDirect and Google Scholar. The selection process utilized a stringent inclusion threshold (≥ 70%) using a Quality Assessment (QA) protocol that synthesized Joanna Briggs Institute (JBI) standards with those proposed by Pingmuang.Results: The thematic synthesis reveals that AI restructures the project lifecycle through three functional typologies: Facilitator (process support), Co-creator (collaborative partner), and Generator (content producer). Quantitative evidence demonstrates that AI-enhanced PjBL yields a large effect size (Cohen’s d = 1.30) in conceptual understanding and a strong positive correlation between digital literacy and creativity (r=0.714). Critical analysis identifies two pathways: a